Contribution to the Implementation of Unmanned Traffic Management System (UTM) Using Distributed Fuzzy Control - Augustin SEMENESCU; Marius MINEA; Ilona Mădălina COSTEA; Ionut CHIVA (Communications of International Proceedings, 2020)
The purpose of this article is to provide a compliance monitoring solution in an unmanned aerial traffic management system (UTM), using fuzzy logic. Fuzzy logic, which is based on the theory of fuzzy sets, allows the linguistic description of the laws of command, operation and control of a system. In working with complex and nonlinear systems it can often be observed that with the increase of their complexity a diminution of the significance of the details in the description of the global behavior of the systems is observed. A detailed description of the behavior of a system is often not only unnecessary, but even counterproductive. One of the consistent arguments for approaching by the methods of sets and vague logics the description of the laws of command and operation of systems is that of the ease of use of linguistic expressions, of the use of words. Finally, we will propose a TMU architecture for the control of the trajectories of unmanned aircraft vehicles (UAS).
Keywords: Unmanned Aircraft Vehicle; System Traffic Management; Fuzzy Logic; Trajectory Monitoring